1998
DOI: 10.2466/pr0.1998.82.3.783
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Suicide Ideation Inventory: Development and Validation

Abstract: We conducted two studies to develop and validate a brief self-report measure for assessing the frequency of positive and negative thoughts related to suicidal behavior. Items on this new measure, the Positive and Negative Suicide Ideation inventory, were generated by undergraduates. In Study 1, we administered a 20-item version of the inventory to 150 male and 300 female undergraduates and conducted an exploratory principal axis factor analysis with varimax rotation. Two factors, Positive Ideation and Negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
97
1
26

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(136 citation statements)
references
References 15 publications
12
97
1
26
Order By: Relevance
“…Osman et al (2002Osman et al ( , 2003 used CFA to investigate the factor structure of the Positive and Negative Suicide Ideation (PANSI) scale. Although the PANSI was developed to measure positive and negative aspects of suicidal ideation (Osman, Gutierrez, Kopper, Barrios, & Chiros, 1998), it contains seven suicide-related items, two death-related items (''felt so unhappy about your relationship with someone you wished you were dead'' and ''felt that life was worth living''), and as noted by Lester (1998), five hopelessness-related items. In their studies of adolescent psychiatric inpatients and high-school students, Osman et al (2002Osman et al ( , 2003 found evidence for a two-factor model in which the first death-related item loaded with the suicide-related items and the second death-related item loaded with the hopelessness-related items.…”
Section: Previous Researchmentioning
confidence: 99%
“…Osman et al (2002Osman et al ( , 2003 used CFA to investigate the factor structure of the Positive and Negative Suicide Ideation (PANSI) scale. Although the PANSI was developed to measure positive and negative aspects of suicidal ideation (Osman, Gutierrez, Kopper, Barrios, & Chiros, 1998), it contains seven suicide-related items, two death-related items (''felt so unhappy about your relationship with someone you wished you were dead'' and ''felt that life was worth living''), and as noted by Lester (1998), five hopelessness-related items. In their studies of adolescent psychiatric inpatients and high-school students, Osman et al (2002Osman et al ( , 2003 found evidence for a two-factor model in which the first death-related item loaded with the suicide-related items and the second death-related item loaded with the hopelessness-related items.…”
Section: Previous Researchmentioning
confidence: 99%
“…Positive and Negative Suicide Ideation Inventory was designed to measure ideations about suicide (Osman et al, 1998). PANSI has two subscales: positive ideation (6 items), which are thoughts that act as the buffer against the suicidal behavior and negative ideations (8 items), which are thoughts, related to suicide.…”
Section: Positive and Negative Suicide Ideation Inventory (Pansi)mentioning
confidence: 99%
“…The coefficient alpha for BHS had been found to be 0.79 with good concurrent, criterion and discriminative validity (Aishvarya, 2014). The cutoff point of 1.67 was used in PANSI to identify patients with suicide ideation as suggested by Osman, et al, (1998). The inclusion criteria were: 18-75 years, Bahasa Melayu or English literate was not treated with CBT and other psychological intervention e.g.…”
mentioning
confidence: 99%
“…The current study validated the factor structure and psychometric properties of the PANSI (Osman et al, 1998) in a sample of clinical outpatients in Malaysia. The results indicated that the data provided a good fit to this particular model.…”
Section: Discussionmentioning
confidence: 99%
“…Osman et al, (1998) reported good internal consistency for PANSI-positive (=.80) and PANSI-negative (=.91) items for a sample of 450 young adults. Meanwhile the confirmatory factor analysis showed that the two-factor oblique model was the best fit in the sample of 286 undergraduates.…”
Section: Introductionmentioning
confidence: 99%